RESEARCH WORK ELASTOMERIC POLYURETHANE TYPE DRAFT GEAR-EPOXY-2, INSTALLED ON THE HIGH-SPEED TRAIN CARS - Pulariia, A. L.; Shatunov, O. V.; Hrichanyi, M. A. (Science and Transport Progress, 2003)
Based on the results of operational and striking tests, an estimation of the possibility of applying elastomeric absorbing devices in Ukrainian high-speed passenger cars has been performed.